Performance determinants of Brazilians international joint ventures - Camelo, Lianna Silva; Forte, Sergio Henrique Arruda Cavalcante (Revista de Administração da UFSM, 2021)
Purpose – Investigate the Joint Venture International performance determinants’ relevance at each point of their life cycle. Design/methodology/approach – Determinants already mapped in the literature were identified and grouped into three dimensions: internal, industrial and institutional. A questionnaire was developed and sent to academics and managers, which requested them to order the dimensions and determinants presented. Data was analyzed using Multi-Attribution Global Quality Inference (MAGIQ). Findings - Results show that the dimensions’ relevance varies according to the organization’s stage in its life cycle. The internal dimension has more influence on performance during the startup period than the industrial and institutional dimensions, but this position is reversed when the IJV becomes mature. Research limitations/implications (if applicable) – This study is based on specialists’ perceptions about IJV’s, so could be a gap between this perception and the facts that the organizational indicators can present. Practical implications – Understanding IJV’s performance determinants’ relevance at each point of their life cycle can help manage these variables to create more efficient actions in accordance to the company’s needs. Originality/value (mandatory) – this study frames performance determinants in the three proposed dimensions within strategic administration theories, ranks them and uses MAGIQ for data analysis.